Text-critical and hermeneutical studies in the Septuagint - Cook, Johann.; Stipp, Hermann-Josef, 1954- (Vetus Testamentum, Supplements, 2012)
Text-critical and Hermeneutical Studies in the Septuagint is the title of a bilateral research project conducted from 2009 to 2011 by scholars from the universities of Munich (Germany) and Stellenbosch (South Africa). The joint research enterprise was rounded off by a conference that took place from 31st of August - 2nd of September 2011 in Stellenbosch. It was held in cooperation with the Association for the Study of the Septuagint in South Africa (LXXSA). Scholars from Germany, the Netherlands, Ireland, Belgium, France, Canada and the USA, as well as South Africa, delivered papers focusing on the history of the LXX; translation technique and text history; textual criticism, and the reception of the Septuagint.